Cultivating students’ communication skills and psychological well-being through Problem Based Learning (PBL) - Danilah Salleh,; Ifa Rizad Mustapa,; Hafizah Abd Mutalib,; Norhaiza Khairudin,; Rozainee Khairudin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Problem Based Learning (PBL) can help developing students’ judgment, creativity, critical thinking, and information integrating abilities. It involves student’s core knowledge, cognitive skills and action skills. The purpose of this study is to examine if the method of PBL may improve students’ communication skills as well as their psychological well-being. The study was conducted using action research methodology in an Accounting class. The study found that students are more active and highly participative during the deliverance of course content. Positive psychological well-being develops students’ constructive attitude toward challenges faced with the use of PBL.